1999
DOI: 10.1006/jfls.1999.0247
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and Force Fluctuations on Isolated Roughened Circular Cylinders of Finite Height in Boundary Layer Flows

Abstract: This paper presents spatio-temporal measurements of a #uctuating pressure "eld acting on isolated roughened cylinders of "nite height in simulated turbulent boundary layer #ows at subcritical Reynolds numbers. The cylinder surface is roughened by placing discrete roughness elements along the height at four circumferential locations. The resulting surface roughness con"guration helps to modify the #ow over the cylinder, which leads to the pressure "eld that exhibits characteristics similar to the transcritical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Naumann and Quadflieg (1972) and Kareem and Cheng (1999) examined flow patterns and spatio-temporal pressure fluctuations on a cylinder when an additional pair of rods was used on the rear surface where the final separation of the shear layer occurs.…”
Section: Article In Pressmentioning
confidence: 99%
“…Naumann and Quadflieg (1972) and Kareem and Cheng (1999) examined flow patterns and spatio-temporal pressure fluctuations on a cylinder when an additional pair of rods was used on the rear surface where the final separation of the shear layer occurs.…”
Section: Article In Pressmentioning
confidence: 99%
“…Okamoto and Sunabashiri (1992) found that the wake behind FCs of small aspect ratio (L=D ¼ 122) is symmetric, but that the wake pattern becomes three dimensional when the aspect ratio exceeds L=D ¼ 4: Farivar (1981) investigated the effect of FC free end on the mean pressure, pressure fluctuations and drag force acting on FC of various aspect ratios exposed to a uniform flow. Regular vortex shedding disappeared for aspect ratios smaller than L=D ¼ 7:5: Kareem and Cheng (1999) investigated the pressure and drag fluctuations for FCs located in a simulated boundary layer. The lateral velocity fluctuations due to strong turbulence intensity of approaching shear flow made a large contribution to the pressure fluctuations, however, the contribution of vortex shedding from the FC was weak.…”
Section: Introductionmentioning
confidence: 99%
“…Tamura et al, 1997;Holmes, 1990;Kareem and Cheng, 1999). Sometimes the results of the analyses appeared encouraging, but there is a general opinion that PCA modes is unable to identify physicallymeaningful CSs (e.g.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 85%